Delayed Presentation of Congenital Diaphragmatic Hernia with Acute Respiratory Distress: Challenges in Diagnosis and Management - Kam Lun Hon; Ronald C. M. Fung; Alexander K. C. Leung (Hindawi Limited, 2020)
Delayed presentation of congenital diaphragmatic hernia (CDH) with acute respiratory distress beyond the newborn period may poise challenges in diagnosis and management. We report a 3-month-old infant who presented with acute-onset respiratory distress and left congenital diaphragmatic hernia that was relieved with thoracoscopic repair. CDH must be differentiated from pneumothorax or pulmonary cyst. Erroneous diagnosis and treatment with thoracocentesis could be disastrous. Pediatricians and surgeons must be aware of this condition to allow early diagnosis and expeditious management. Subcutaneous emphysema should not be misdiagnosed as pneumothorax and management is expectant.